English as medium of instruction (MOI) in classroom activities: Teachers’ perceptions from eastern Indonesia - Sahril Nur; Auliyanti Sahril Nurfadhilah; Eva Meizara Puspita Dewi; Jamilah (JOALL (Journal of Applied Linguistics and Literature), 2023)
English as the Medium of instruction (MOI) in Indonesia has experienced up and down periods, thus affecting the teachers’ use of code-switching and code-mixing strategies. This article reports on English teachers’ perceived usefulness of English as the Medium of Instruction (MOI) in classrooms. Participants of the study are English teachers from various school levels in one province in Eastern Indonesia. This exploratory case study used a self-assessment survey as the single instrument. As a result, teachers have a positive perception toward English as the Medium of Instruction (MOI) as they believe it could improve students’ proficiency. However, some are hesitant and would rather have classes taught in a blend of their native language and English. This study implies that teachers should consider elements of high-quality instructions. This study suggests developing an institutional ELT policy to infuse MOI into classroom pedagogy.